Constraint-based form-finding of space trusses for Injection 3D Concrete Printing through Vector-based Graphic Statics - Xiao, Yinan; Hack, Norman; Kloft, Harald; Lowke, Dirk; Mai, Inka; D’Acunto, Pierluigi (Additive manufacturing, 2025)
This paper presents a form-finding approach for Injection 3D Concrete Printing (I3DCP) using Vector-based Graphic Statics (VGS). This approach adopts a top-down strategy, initiating a preliminary global design in the form of a space truss and integrating structural and fabrication constraints specific to I3DCP. A form-dependent self-weight load is applied throughout the form-finding process until the structure achieves static equilibrium. As the current I3DCP setup is mounted on a robotic arm with a stationary base, the feasibility of the designed structure for I3DCP is assessed, ensuring compatibility with the robotic arm’s workspace. Structures exceeding the workspace boundaries are segmented and individually optimised, subject to topological and geometrical constraints. The optimised segments are then merged into a single assembly to complete the process. This approach is demonstrated through the design and construction of a 3-metre-span pedestrian bridge. This prototype is 3D scanned and then analysed via the finite element method to evaluate its mechanical performance. [Display omitted] •A VGS-based design workflow for I3DCP of space trusses.•Material and manufacturing parameters from experiments applied to design workflow.•Form-dependent self-weight implemented in VGS-based form-finding method.•Topological and geometrical adjustment strategies developed for I3DCP.•A 3-metre pedestrian bridge prototype built and structurally examined through FEA.